"Dump the paper quiz"—The PERI model for exploring gamification in student learning in the United Arab Emirates. Issue 5 (October 2022) - Yasin, Naveed; Majid Gilani, Sayed Abdul; Nair, Gayatri
This paper explores the effects of gamification (a game-based student response system) on student learning in the United Arab Emirates (UAE). The data, collected through a series of semi-structured in-depth interviews with 32 learners, were analyzed using qualitative thematic analysis (i.e., template analysis). Based on an in-depth analysis of the data using NVIVO 10, the authors propose and apply the "PERI" model to develop multi-focal insights into gamification and its influences on student learning. The model proposed is original and comprehensive, encompassing (1) Preferabilities (P), (2) Experiences (E), (3) Recommendations (R), and (4) Impressions (I). Although most of the findings were positive with regard to application and receptivity across all dimensions of the PERI model for the gamification tool—a game-based student response system (GSRS) used for delivering education—they also reveal areas in need of development for the successful embedding of gamifying technology–enhanced learning provisions and their efficacy in teaching and learning pedagogy. The conclusions of this study outline implications for educators, students, education leaders, and gamification product developers.